NGHIÊN CỨU TỔNG HỢP POLYME DẪN ĐIỆN POLYANILIN (PANI) - Công, Vũ Tiến; Thảo, Phạm Mạnh; Hùng, Dương Công (Vietnam Journal of Chemistry, 2012)
The paper presents a process of synthesizing conductive polymers from an aromatic amine as aniline. The process provides simple synthesizing steps for the polyaniline salt by polymerizing aniline in the presence of different protonic acids as dopants such as hydrochloric, maleic, and 5-sulfosalicylic acids. The synthesized polyaniline salts have electrical conductivity as high as 4 S.cm-1 and the yield of polyaniline was higher than 61 percent in all cases and up to 90 percent. A process for preparing of PANI, which dissolves in organic solvent of chloroform is also presented.